Anatomic reconstruction of the acromion in cases of traumatic fractures after reverse shoulder arthroplasty. Report of a series of cases - Stückelberger, Galo; Knoth, Christoph; Zettl, Ralph; Jaberg, Laurenz (Revista Colombiana de Ortopedia y Traumatología, 2020)
Aim: To propose a surgical technique to treat the traumatic acromion fractures, as well as acromion fractures before reverse total Shoulder Replacement (TSR). Methods: Six patients were treated with the same fixation technique between December 2013 and December 2016. Three patients had acromial insufficiency fractures (type II) following TSR (Group A). The other three patients, who had traumatic acromion fractures, underwent unsuccessful conservative treatment (Group B). Surgical treatment involved reconstruction of the acromion using an open technique with plate and interfragmentary screw fixation. Results: Following reconstruction, shoulder function was regained in all patients in Group A. Forward flexion increased, on average, from 53º to 127º , and abduction improved from 52º to 125º. Measurements at one-year follow-up were Constant scores from 55-71, and subjective shoulder value (SSV) from 50-90. In Group B, preoperative range of motion was not substantially diminished. Forward flexion improved from 133º to 157º, and abduction increased from 147º to 153º. One year following surgery, the Constant scores in Group B ranged from 70-86, and SSV was 80-100. All three patients performed daily activities without pain, and were able to return to work. Plate removal was necessary in half the patients in the cohort (Group A n = 1; Group B n = 2). Conclusion: An acromion fracture is a serious condition that can cause significant damage to shoulder functioning. In patients with or without previous TSR, this fixation technique was used successfully to reconstruct the anatomic lateral and basal acromion. Evidence Level: IV